Paranasal Sinus Mucoceles and their Ocular Impacts: A case report - Li, Ziqing (Canadian Journal of Optometry, 2024)
Introduction: Paranasal sinus mucoceles are the build-up of mucous-containing, epithelium-lined, cystic lesions within the air-filled cavities in the bones surrounding the nasal cavity. An accumulation of mucous can occur in the sinus cavity when the normal drainage pathways are blocked, resulting in an increased volume of mucous. Case report: A 56-year-old Hispanic male complained of proptosis, periorbital edema, and pain in the right eye, accompanied by cluster headaches persisting for the past six months. Initial examination demonstrated uncorrected visual acuity of 20/20 in both eyes at distance and near. Clinical assessments further revealed Hertel exophthalmometry measurements of 21 mm in the right eye and 19 mm in the left (base of 108 mm), along with resistance to manual pressure in the affected right eye. Subsequent computed tomography imaging of the head and orbits identified a sizable, well-defined mass originating from the right nasal cavity, extending into multiple paranasal sinuses, and inducing structural alterations in the medial wall of the maxillary sinus, consistent with paranasal sinus mucoceles. Conclusion: Proptosis and lid edema can arise from various etiologies, encompassing intracranial masses, autoimmune disorders, or impaired venous return. This case report adds another consideration of a diagnosis in a patient with a history of sinus surgery. Comprehensive history gathering and meticulous clinical examination are paramount to discerning pathological manifestations in establishing an accurate diagnosis.